Biens publics : construction économique et registres sociaux - Philippe Boudes; Catherine Darrot (Revue de la Régulation)
This paper considers a non-economic approach of public goods to address their social construction and the variety of dimensions that constitute them. The first part presents the classical definitions of public goods and, inspired by the Kuhnian epistemological approach, describes the labelization process and reappropriation of public goods made by the neoclassical theory. The second part shows the main difficulties that this labeling encounters: it limits the reading of public goods to the only individual rationality, it considers such goods as demoralized and, from a practical point of view, it prevents their fully legitimate designation. The third part focuses on the social construction of these goods. On the one hand we mobilize and expand the process goods publicness proposed by Kaul and Mendoza (2003). On the other hand, we associate to the conceptual and economic reality of public goods a normative dimension and ontological dimension. These distinctions, which we observe as recurrent in the work of analysis of public goods, reflect the diversity of frameworks used to define these goods. These must be differentiated, and sociological works invite us to do so, as they designate a reality by essence, purpose or ontology. It is the inclusion of this framework which allows to embrace the process of publicizing, and which recalls, once again, the need to take into account the social dynamics when analyzing the public goods construction.public goods, economics, sociology, labellization, publicness, social construction